Feasibility of a Home-Based Action Observation Training for Children With Unilateral Cerebral Palsy: An Explorative Study - Beani, Elena; Menici, Valentina; Ferrari, Adriano; Cioni, Giovanni; Sgandurra, Giuseppina (Frontiers in Neurology, 2020)
Unilateral Cerebral Palsy (UCP), the most frequent form of Cerebral Palsy, usually affects more the upper limb (UL) than the lower limb. Rehabilitation programs are addressed to improve manual abilities and UL use. In recent years, Information and Communication Technology (ICT) has been introduced in rehabilitation to increase treatment opportunities for patients, and also in home-based intervention. Moreover, the discovery of the Mirror Neuron System allowed to insert a new paradigm of treatment that is the Action Observation Training (AOT). The aim of the present study was to investigate the feasibility of a new rehabilitative home-based approach, called Tele-UPCAT (Tele-monitored UPper Limb Children Action Observation Training), based on the principles of AOT, in a group of Italian children and adolescents with UCP. This investigation was to provide information about the possibility of introducing ICT in telerehabilitation field. Twenty-nine children aged 11.73 ± 3.65 years (range 6.00–18.75) with a diagnosis of UCP participated in the study. They carried out 15 days of training based on the AOT paradigm with Tele-UPCAT system while wearing Actigraphs on both wrists. The feasibility of both training and study design and procedures was assessed through nine criteria taken from existent literature and from a questionnaire designed and realized ad hoc for the purpose, based on standard items of usability and acceptability. All feasibility criteria were met: 80% of training sessions were completed in the planned time and no significant technical issues were found. From the questionnaire, total scores were all above 82.15%, while the four sections obtained the following scores: (i) customization of exercises 80.00%; (ii) acceptability at home, 77.50%; (iii) required effort 80.00%; and (iv) suitability of manual and software 95.00%. No differences were found for age and sex. Tele-UPCAT demonstrated to be feasible as a home-based AOT for children and adolescents with UCP. Trial registration NCT03094455.